2020
DOI: 10.7759/cureus.8280
|View full text |Cite
|
Sign up to set email alerts
|

Heyde’s Syndrome Complicating Management in a Patient With High Bleeding and Thrombotic Risks

Abstract: The association of severe aortic stenosis and gastrointestinal (GI) bleeding is a well-known phenomenon. The pathogenesis involves an acquired deficiency of von Willebrand factor (vWF) due to shear stress resulting in alteration of vWF morphology. This results in inappropriate cleavage of vWF multimers into smaller dysfunctional fragments. Patients with atrial fibrillation and high thrombotic risk require anticoagulation for stroke prophylaxis. We describe a case of severe intermittent GI bleeding in a patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
0
1
Order By: Relevance
“…Hudzik et al [5] reported an 82-year-old man with a bleeding colon who survived 12 months. Our patient survived longer than those in all previous reports [3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18]. However, our patient developed Heyde's syndrome after cardiac surgery, and we could not perform further cardiac interventions.…”
Section: Discussion/conclusioncontrasting
confidence: 57%
“…Hudzik et al [5] reported an 82-year-old man with a bleeding colon who survived 12 months. Our patient survived longer than those in all previous reports [3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18]. However, our patient developed Heyde's syndrome after cardiac surgery, and we could not perform further cardiac interventions.…”
Section: Discussion/conclusioncontrasting
confidence: 57%